2002
DOI: 10.1029/2001pa000749
|View full text |Cite
|
Sign up to set email alerts
|

Accurate estimation of sea surface temperatures using dissolution‐corrected calibrations for Mg/Ca paleothermometry

Abstract: [1] Paired d 18O and Mg/Ca measurements on the same foraminiferal shells offer the ability to independently estimate sea surface temperature (SST) changes and assess their temporal relationship to the growth and decay of continental ice sheets. The accuracy of this method is confounded, however, by the absence of a quantitative method to correct Mg/Ca records for alteration by dissolution. Here we describe dissolution-corrected calibrations for Mg/Ca-paleothermometry in which the preexponent constant is a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
203
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(217 citation statements)
references
References 20 publications
9
203
0
3
Order By: Relevance
“…After applying a dissolution correction based on foraminiferal test weights, Mg/Ca-based temperatures were in good agreement with alkenone-based temperatures. This result suggests that the correction of Rosenthal and Lohmann (2002) is valuable for dissolution caused by metabolic respiration within sediments. A possible limitation of this method is the observation that initial test weights of several species of planktonic foraminifera vary both regionally and temporally (Barker and Elderfield, 2002).…”
Section: Effects Of Partial Dissolutionmentioning
confidence: 77%
See 1 more Smart Citation
“…After applying a dissolution correction based on foraminiferal test weights, Mg/Ca-based temperatures were in good agreement with alkenone-based temperatures. This result suggests that the correction of Rosenthal and Lohmann (2002) is valuable for dissolution caused by metabolic respiration within sediments. A possible limitation of this method is the observation that initial test weights of several species of planktonic foraminifera vary both regionally and temporally (Barker and Elderfield, 2002).…”
Section: Effects Of Partial Dissolutionmentioning
confidence: 77%
“…Broecker and Clark, 2001b;Broecker et al, 2001). Rosenthal and Lohmann (2002) demonstrated that the pre-exponential constant, B, in the Mg/Ca temperature calibration equation (Eq. (1)) varied as a function of test weight during dissolution for the tropical species G. ruber (w) and G. sacculifer.…”
Section: Effects Of Partial Dissolutionmentioning
confidence: 99%
“…Mg / Ca (mmol mol-1) = Be AT A temperature sensitivity of ~9% change in Mg/Ca per degree Celsius is indicated by published 'A' values of 0.09±0.01 °C -1 Dekens et al, 2002;Rosenthal and Lohmann, 2002). Species-specific effects are primarily expressed by the range of pre-exponential constants ('B') from 0.31-0.52 (Dekens et al, 2008) which determine absolute temperature calculations (Rosenthal, 2007).…”
Section: Mg/ca In Planktonic Foraminiferamentioning
confidence: 99%
“…Approximately 15 individuals (N = 4-29) were crushed and cleaned for minor elemental analyses. Samples were cleaned using a standard protocol that included repetitive Milli-Q water and methanol rinses, oxidative and reductive cleaning steps, and a weak acid leach (Martin and Lea, 2002;Rosenthal and Lohmann, 2002). Cleaned samples were measured on a PerkinElmer Optima 8300 inductively coupled plasma-optical emission spectrometer (ICP-OES) (Wara et al, 2003).…”
Section: Methodsmentioning
confidence: 99%